Factors associated with household food security of participants of the MANA food supplement program in Colombia - Hackett, Michelle; Melgar-Quiñonez, Hugo; Taylor, Christopher A.; Alvarez Uribe, Martha Cecilia (Archivos Latinoamericanos de Nutrición (ALAN), 2021)
The objective of this study was to explore demographic and economic characteristics associated with household food security of 2,784 low-income households with pre-school aged children receiving food supplements from the Colombian Plan for Improving Food and Nutrition in Antioquia -MANA (Mejoramiento Alimentario y Nutricional de Antioquia) in the Department of Antioquia, Colombia. Included in the study was a 12-item household food security survey was collected from a cross-sectional, stratified random sample of MANA participants in which households were characterized as food secure, mildly food insecure, moderately food insecure, and severely food insecure. It was hypothesized that household food security status would be strongly associated with demographic characteristics, food expenditure variables, and food supplement consumption by children in MANA. Food insecure households were characterized by more members, older parents, and lower income (p<0.0001). Rural residence and female head of households had higher rates of food insecurity (p<0.01). Food insecure households had the lowest monthly expenditures food (p<0.0001). Severely food insecure households saved the highest percentage of per capita food expenditure from consuming MANA supplements (p<0.0001), similarly, MANA food supplement intakes were greatest in households reporting the most food insecurity (p<0.001). The results of this study are important to describe characteristics of the population benefiting from the MANA nutrition intervention by their unique level of household food security status. El objeto de este estudio fue explorar la asociación de la inseguridad alimentaria en el hogar con las características demográficas, el gasto alimentario del hogar y el consumo del complemento alimentario de 2,784 hogares de bajos ingresos con niños preescolares que recibían el complemento alimentario de MANA (Programa de Mejoramiento Alimentario y Nutricional de Antioquia) en el Departamento de Antioquia, Colombia. En los hogares seleccionados mediante un muestreo probabilístico, se aplicó una escala de seguridad alimentaria compuesta por 12 ítems. Los hogares fueron clasificados como seguros, y con inseguridad alimentaria leve, moderada o severa. Se hipotecaron que el estado de seguridad alimentaria seria asociado de una manera fuerte con las características demográficas, el gastos alimentarias, y el consumo del complemento por los niños participantes en MANA. Los hogares con inseguridad alimentaria estaban compuestos por un mayor número de personas, los padres eran de mayor edad, y tenían menores ingresos y menor gasto alimentario (p<0.0001). Los hogares del área rural y encabezados por mujeres presentaron mayores porcentajes de inseguridad alimentaria (p<0.01). Los hogares con inseguridad alimentaria severa presentaron el porcentaje más alto de gasto alimentario (p<0.0001), de la misma manera, el consumo del complemento de MANA fue más alto en los hogares que reportaron inseguridad severa (p<0.001). Los resultados son importantes para describir las características de la población que se beneficie de la intervención nutricional de MANA por su nivel de seguridad alimentaria en el hogar.